Maintaining taxonomic accuracy in genetic databases: A duty for taxonomists—Reanalysis of the DNA sequences from Mercan et al. (2024) on the genus Potamothrix (Annelida, Clitellata) in Turkish lakes - Vivien, Régis; Martin, Patrick (Zootaxa, 2025)
Public DNA sequence databases such as GenBank are widely used for identification of organisms in ecological and taxonomic studies. It is important that these public databases contain as few mistakes as possible and that any errors detected in these databases are reported. Here, we reanalyzed the COI sequences of Mercan et al. (2024) and showed that they were mistakenly considered by these authors as belonging to different populations (haplotypes) within the species Potamothrix hammoniensis (Tubificinae). We found that they corresponded to four distinct Tubificinae lineages (species), Pothamothrix alatus paravanicus, Potamothrix bavaricus, Tubifex sp. and Potamothrix sp. Despite these identification errors, the data from Mercan et al. (2024) remain interesting as they provide new information on the diversity of the genus Potamothrix in Turkey. Prompt measures must be taken to correct these errors and prevent them from being detrimental to future studies.